Negative Moods as the Only Possible Locus of Ontological Experience - Luks, Leo (Problemos, 2020)
This article is a Heideggerian inquiry into the possibility of ontological experience, that is, the possibility of experiencing the ontological difference, something wholly distinct from beings. Heidegger, as we know, articulated this as the question of Being. It is a paradoxical question that cannot, at first sight, be answered phenomenologically (in the Husserlian style): if any conscious experience presupposes the constitution of an intentional object in the act of experience, there must be something in any experience. In this article, I set out to defend the position that ontological experience is possible and central to the human existence. This view rests on the Heideggerian notion of the affective grounds of all thinking, the attunement of any experience by moods. I will argue that: 1) any thinking is attuned by moods; 2) ontological experience (i.e. experiencing something wholly distinct from beings) occurs in certain negative moods. 3) ontological experience is possible only through failure, a malfunction in the fulfilment of meaning; 4) ontological experience is possible in art rather than in science (or in some rigorous philosophy).